2015
DOI: 10.1111/lam.12434
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of adhesion, aggregation and surface charges of Lactobacillus strains derived from the human oral cavity

Abstract: Adhesion to host tissues and bacterial aggregation (auto- and coaggregation) are the highly important criteria for selecting strains with probiotic potential. These abilities are commonly involved with surface-charged characteristics. This is the first study to investigate the oral Lactobacillus species using an oral keratinocyte cell line. Significant results were found for the correlations between the adhesion and surface charge characteristics and for aggregation among certain strains of Lactobacillus gasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 35 publications
4
38
1
Order By: Relevance
“…In our study zone of inhibition may have formed because the probiotics have inhibited the periodontal pathogen's active multiplication the same way. 19,20 A study by Morales A, et al showed the additional use of L. Rhamnosussachets provided similar results when compared with scaling and root planning, thus showing benefit of probiotics. 21 One of the suggested mechanism stated by Hojo et al says that lactobacillus acidophilus and P. gingivalis compete with each other for vitamin K and inhibits the growth of latter by possibly competing for the growth factor in a co-culture.…”
Section: Discussion:-mentioning
confidence: 96%
See 1 more Smart Citation
“…In our study zone of inhibition may have formed because the probiotics have inhibited the periodontal pathogen's active multiplication the same way. 19,20 A study by Morales A, et al showed the additional use of L. Rhamnosussachets provided similar results when compared with scaling and root planning, thus showing benefit of probiotics. 21 One of the suggested mechanism stated by Hojo et al says that lactobacillus acidophilus and P. gingivalis compete with each other for vitamin K and inhibits the growth of latter by possibly competing for the growth factor in a co-culture.…”
Section: Discussion:-mentioning
confidence: 96%
“…13 In our study, the increased zone of P. gingivalis in culture containing lactobacillus might be due to a result of the increased level of probiotics. 18 Piwat et al 19 conducted an in-vitro study which explains how adhesion, aggregation and co-aggregation mechanisms of probiotic bacteria can influence the growth of other periodontal pathogens. These organisms attach to the oral hard tissues more strongly than pathogens, by competing for the adhesion surfaces.…”
Section: Discussion:-mentioning
confidence: 99%
“…Furthermore, they modulate the inflammatory response (humoral and cellular) and produce substances such as lactic acid, hydrogen peroxide and bacteriocins (antimicrobial agents produced by lactic acid bacteria, whose action provides them of the probiotic effect) (8,13,30). Most of the studies reviewed mention its ability to compete with pathogens for adhesion surfaces and nutrients, causing the displacement of the latter ones (15,16). …”
Section: Discussionmentioning
confidence: 99%
“…It has also been mentioned a possible decrease of pro- inflammatory cytokines, collagenases, elastases and prostaglandins E2 levels (40). Piwat S, et al (15) conducted an in-vitro study that, despite not meeting our inclusion criteria, deserves to be commented because it is one of the few jobs that explains the adhesion, aggregation and co-aggregation mechanisms of probiotic bacteria, and their influence in the probiotic effect. In theory, probiotic bacteria attach to the oral tissues more strongly than pathogens, being able to compete for adhesion surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation